Tradisi Bebantai Menyambut Bulan Ramadan dalam Masyarakat Merangin Jambi - Alhusni, Alhusni (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2014)
Ramadhan as the holy month for Muslims greeted with joyful. The majority of Merangin society were farmers. They domesticated livestock for slaughter. This studied would explore the traditions that done by Merangin society in welcoming Ramadan month. Besided Bebantai, Merangin community also commonly performed a clean village, istighosah,and eat together, while praying together asking for fluency in welcoming and fasting Ramadan.